Characteristics of Obstructive Sleep Apnea Across the Spectrum of Glucose Tolerance in Obese Adolescents - Hannon, Tamara S.; Watson, Sara E.; Jalou, Hasnaa E.; Chakravorty, Sangeeta; Mather, Kieren J.; Arslanian, Silva A. (Frontiers in Endocrinology, 2018)
Background: It is not known if dysglycemia and sleep-disordered breathing are linked in adolescents, as in adults. Objective: To evaluate measures of sleep-disordered breathing across the spectrum of glucose tolerance in obese adolescents. We hypothesized that dysglycemia would be associated with sleep-disordered breathing. Participants/Methods: This was a prospective, cross-sectional clinical study that included 57 adolescents (BMI 38.98.4 kg/m2) aged 12-18 years (14.5±1.6) with normal glucose tolerance (NGT), or dysglycemia (impaired glucose tolerance [IGT] or type 2 diabetes [T2D]). Measures: Anthropometrics, overnight polysomnogram (PSG), and oral glucose tolerance tests (OGTT) were performed. Participant characteristics and outcome measures were compared by glucose tolerance status. Correlational analyses were conducted to assess the associations between variables of interest. Results: Participants with dysglycemia (n=21) were not different from those with NGT (n=36) for BMI, waist circumference, body fat, or sleep characteristics. Nocturnal oxygen desaturation was associated with higher BMI (r = -0.334, p = 0.012). The apnea-hypopnea index (AHI) was not associated with physical and metabolic parameters. Although participants with T2D tended to have higher AHIs (median 3.2, 2.2, and 1.6 events/hour for T2D, IGT, and NGT, respectively) there was not a linear relationship between measures of glycemia and AHI. Conclusion: Further study with a larger proportion of youth with prediabetes and T2D is necessary to determine whether evaluation for sleep-disordered breathing is uniformly warranted.